Reinventing government : what a difference a strategy makes - Osborne, David ([UN] [New York]US, 2007)
Suggests the use of five strategies for reinventing public institutions, each with several distinct approaches and many tools. The strategies suggested are: the Core Strategy which uses the lever of power; the Consequences Strategy whose lever is incentives; the Customer Strategy using the lever of accountability; the Control Strategy using power as its lever; and finally, the Culture Strategy whose lever is culture. Looks at whether this reinvention would work in developing nations.